PENGARUH PELAYANAN MA AL-CHOLILI TERHADAP KEPUASAN SISWA - Dassucik Dassucik (STKIP PGRI SITUBONDO, 2014)
Satisfaction of the buyer depends on the employee’s performance in meeting the expectations of buyers. Services to be a way to attract and provide a satisfaction to customers, which it can be measured by customer satisfaction. satisfaction of a person's feelings of pleasure or disappointment that emerged after comparing the performance of the products considered against the expected performance if the performance is below expectations, the customer is not satisfied, if the performance meets expectations, the customer is satisfied, if performance exceeds expectations, the customer is very satisfied. This study aims to determine whether there is influence MA AL - Cholili services to student satisfaction. This research is a quantitative study, the method of data collection using questionnaires, documentary, observation and interviews. The subjects were students of MA Al-Cholili class X until to class XII with a population of as many as 30 students. Data analysis using SPSS version 17.0 for windows. Hypothesis testing to determine the effect of MA Al-Cholili services to student satisfaction with the results of F = 2502.886668 > F = 4.195971707 then H0 is rejected or accepted Ha. Or it could be by comparing the P-value = 0.000 < α = 0.05, then the Ha received therefore MA Al-Cholili services affect student satisfaction percentage of MA Al-Cholili services according to the results output by 98.9 %, the percentage of MA Al-Cholili service is suggests that the effect of MA Al-Cholili services to a very high student satisfaction effect can be interpreted MA Al-Cholili services to the satisfaction of students having the effective contribution of 98.9 %. Student satisfaction can be derived from services deduced MA Al-Cholili are either in the process of learning or other activities.